Binding to gold nanoclusters alters the hydrogen bonding interactions and electronic properties of canonical and size-expanded DNA base pairs1. Issue 61 (4th July 2015) - Rai, Sandhya; Singh, Harjinder; Priyakumar, U. Deva
<x xml:space="preserve">Abstract</x> Structural perturbations, in terms of size expansion and metal binding, lead to exciting electronic properties which can be exploited in designing novel nano-electronic devices.